ChemInform Abstract: Dehydrogenative N‐Heterocyclization of 2‐(2‐Aminoaryl)ethyl Alcohols to Indole Derivatives Catalyzed by (μ‐Oxo)tetraruthenium Cluster/1, 2‐Bis(diphenylphosphino)benzene. Issue 17 (4th April 2013) - Kondo, Teruyuki; Kanda, Takashi; Takagi, Daisuke; Wada, Kenji; Kimura, Yu; Toshimitsu, Akio
Abstract The novel title catalyst system enables a simple, selective, and practical synthesis of indoles from aminoalcohols.